2021
DOI: 10.7759/cureus.15928
|View full text |Cite
|
Sign up to set email alerts
|

Massive Mixed Adenoneuroendocrine Carcinoma: A Case Report

Abstract: Mixed adenoneuroendocrine carcinoma (MANEC) of the gastrointestinal (GI) tract is a rare subtype of mixed tumors, and it is scarcely described in the literature. MANEC tumors are composed of adenocarcinoma and neuroendocrine carcinoma components, each of which comprises at least 30% of the lesion. Diagnosing MANEC requires specific histological and immunohistochemistry (IHC) analysis. Typically, MANEC tumors carry a poor prognosis due to their very aggressive nature.We report the case of a 70-year-old female p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…It has also been shown that cisplatin/5-FU in combination with etoposide is a common chemotherapy regimen used for the treatment of MiNENs, similar to that used for adenocarcinomas ( 76 ). The prognosis of patients with MiNENs tumours that have spread to distant places can be considerably improved via a combination of surgical removal of each metastasis and systemic treatment ( 77 ). The prolongation of progression-free survival in patients with metastatic neuroendocrine tumours can be achieved by the appropriate utilization of systemic chemotherapy in conjunction with somatostatin analogues, such as octreotide and lanreotide ( 8 ).…”
Section: Treatment Of Gastric Minensmentioning
confidence: 99%
“…It has also been shown that cisplatin/5-FU in combination with etoposide is a common chemotherapy regimen used for the treatment of MiNENs, similar to that used for adenocarcinomas ( 76 ). The prognosis of patients with MiNENs tumours that have spread to distant places can be considerably improved via a combination of surgical removal of each metastasis and systemic treatment ( 77 ). The prolongation of progression-free survival in patients with metastatic neuroendocrine tumours can be achieved by the appropriate utilization of systemic chemotherapy in conjunction with somatostatin analogues, such as octreotide and lanreotide ( 8 ).…”
Section: Treatment Of Gastric Minensmentioning
confidence: 99%